2017
DOI: 10.1523/jneurosci.3007-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Orai1 Plays a Crucial Role in Central Sensitization by Modulating Neuronal Excitability

Abstract: Pathological pain is a common and debilitating condition that is often poorly managed. Central sensitization is an important mechanism underlying pathological pain. However, candidate molecules involved in central sensitization remain unclear. Store-operated calcium channels (SOCs) mediate important calcium signals in nonexcitable and excitable cells. SOCs have been implicated in a wide variety of human pathophysiological conditions, including immunodeficiency, occlusive vascular diseases, and cancer. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 50 publications
2
51
0
Order By: Relevance
“…In a series of experiments employing Orai1 knock-out animals, Dou et al. 121 showed that Orai1 contributed to neuronal hyperexcitability in the spinal cord and pain behaviors following formalin and carrageenan administration. In the periphery, knockdown of STIM1, STIM2, Orai1, and Orai3 were found to diminish SOCE in DRG neurons.…”
Section: Er Ca 2+ Regulation and The Impact On Paimentioning
confidence: 99%
“…In a series of experiments employing Orai1 knock-out animals, Dou et al. 121 showed that Orai1 contributed to neuronal hyperexcitability in the spinal cord and pain behaviors following formalin and carrageenan administration. In the periphery, knockdown of STIM1, STIM2, Orai1, and Orai3 were found to diminish SOCE in DRG neurons.…”
Section: Er Ca 2+ Regulation and The Impact On Paimentioning
confidence: 99%
“…All three subunits are expressed both in neurons and glial cells [ 11 , 37 , 42 , 44 , 45 , 46 , 47 ]. In neurons, ORAI1 appears dispensable for SOCE [ 46 ], but it has been implicated in neuronal excitability [ 45 , 48 ], whereas ORAI2 seems to be part of a neuronal SOC (nSOC) based on TRPC6 and activated by STIM2, and its activity is impaired in mouse AD models [ 46 ]. In glial cells, SOCE plays a major role in the Ca 2+ -based excitability that characterizes these cells both in culture [ 14 , 42 , 47 , 49 ] and in situ [ 50 , 51 ] studies.…”
Section: Introductionmentioning
confidence: 99%
“…STIM1 and STIM2 are upregulated in the hippocampus of chronic epileptic mice and were found to be strongly expressed in hippocampal samples from a patient suffering from medial temporal lobe epilepsy [126]. This highlights a role for SOCE in somehow controlling neuronal network excitability, as proposed for dorsal horn neurons [127]. Expression of these two ER proteins was also found to be upregulated after induction of TBI in two different studies.…”
Section: Neuronal Store-operated Calcium Entry (Soce) and Its Rolementioning
confidence: 95%